INCIDENCE OF DAMAGE, BIOLOGICAL CYCLE and MORPHOLOGY OF THE CAMU CAMU BRANCH AND TRUNK BORER Timocratica albella Zeller, 1839 (LEPIDOPTERA: DEPRESSARIIDAE) (Revista de Investigación Intercultural ASAMPITAKOYETE, 2025)
Timocratica albella (Lepidoptera: Depressariidae) is a pest that causes severe damage to the branches and trunk of camu camu trees in the Peruvian Amazon. The aim of this study was to describe the incidence of damage, biological cycle and morphology of the different developmental stages of this camu camu branch and trunk borer. The study was conducted in camu camu plots in the hamlets of Padre Bernardo and Nueva Esperanza de Panaillo, in Yarinacocha, Ucayali, Peru. The incidence of T. albella damage was assessed using a row sampling method within one hectare of plot per hamlet. The life cycle was determined under laboratory conditions at an average temperature of 28°C and 58–60% relative humidity. The percentage of damage was 91–95% in Padre Bernardo and 47–64% in Nueva Esperanza de Panaillo. The total duration of the T. albella life cycle averaged 207.8 days; the egg stage lasted 11.5 ± 0.9 days; the larval stage had nine instars lasting 164.8 ± 6.0 days; the pupal stage lasted 25.6 ± 8.9 days; and the adult stage lasted 5.7 ± 1.0 days. T. albella larvae consumed 21 to 78 cm² of the outer bark (rhytidome) throughout their development and were particularly voracious in the final instar. The described morphological characteristics allow for the identification of the developmental stages and sexual dimorphism of adult T. albella in the field.
Keywords: Myrciaria dubia; insect pest; morphology; incidence; biology